An Improved Synthetic Process of Two Key Intermediates and Their Application in the Synthesis of Lifitegrast - Jiang, Gang-Long; Wang, Xin-Kun; Xiao, Xiao-Fei; Liu, Yu (Pharmaceutical Fronts, 2023)
Benzofuran-6-carboxylic acid 2 and 2-(tert-butoxycarbonyl)-5,7-dichloro-1,2,3,4-tetrahydroisoquinoline-6-carboxylic acid 21 are two key intermediates for the synthesis of lifitegrast (1). The present study aimed to obtain lifitegrast from the key intermediates of 2 and 5,7-dichloro-2-(2,2,2-trifluoroacetyl)-1,2,3,4-tetrahydroisoquinoline-6-carboxylic acid (31), which had the same core structure as 21. In this study, the synthetic routes of 2 and 31 were explored. 2 and 31 were synthesized from 4-bromo-2-hydroxybenzaldehyde (25) and 2-(2,4-dichlorophenyl)ethan-1-amine (28), with the yields of 78 and 80%, respectively. The route avoided the harsh reaction conditions of generating 2 in a previous study and could more efficiently achieve the core structure of 5,7-dichloro-1,2,3,4-tetrahydroisoquinoline-6-carboxylic acid. Besides, the hydrolysis reaction conditions of preparing lifitegrast were also optimized. In this work, lifitegrast was obtained from 2 and 31 with high purity (>99.9%) and an overall yield of 79%, which was higher than the reported yield of 66%.
Keywords: lifitegrast; benzofuran-6-carboxylic acid; 5,7-dichloro-1,2,3,4-tetrahydroisoquinoline-6-carboxylic acid; improved synthetic process